The implications of programme assessment patterns for student learning - Jessop, Tansy; Tomas, Carmen (Assessment and evaluation in higher education, 2017)
Evidence from 73 programmes in 14 U.K universities sheds light on the typical student experience of assessment over a three-year undergraduate degree. A previous small-scale study in three universities characterised programme assessment environments using a similar method. The current study analyses data about assessment patterns using descriptive statistical methods, drawing on a large sample in a wider range of universities than the original study. Findings demonstrate a wide range of practice across programmes: from 12 summative assessments on one programme to 227 on another; from 87% by examination to none on others. While variations cast doubt on the comparability of U.K degrees, programme assessment patterns are complex. Further analysis distinguishes common assessment patterns across the sample. Typically, students encounter eight times as much summative as formative assessment, a dozen different types of assessment, more than three quarters by coursework. The presence of high summative and low formative assessment diets is likely to compound students' grade-orientation, reinforcing narrow and instrumental approaches to learning. High varieties of assessment are probable contributors to student confusion about goals and standards. Making systematic headway to improve student learning from assessment requires a programmatic and evidence-led approach to design, characterised by dialogue and social practice.